2020
DOI: 10.1155/2020/1649759
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Endocrine Changes Determined in Saliva of Adolescents Engaged in Computer Gaming

Abstract: Passion for computer games negatively affects the health level of schoolchildren. Among the approaches to monitoring the functional state of such schoolchildren, the most informative and painless is the study of the saliva. The study involved 45 children, aged 14.00 ± 0.21 years, and divided according to the contact’s intensity with computer games. The following indicators of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Several cognitive domains appear to be sensitive to changes in serotonin such as memory, attentional functions notably focused and sustained attention, and cognitive flexibility (Schmitt et al, 2006;. Podrigalo et al (2020) examined the metabolic and endocrine changes of forty-five schoolboys engaged in computer gaming. The participants were divided into two groups: the active players' group (n=26) and the control group which consisted Research, Society and Development, v. 12, n. 2, e20512239568, 2023 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v12i2.39568 of 19 schoolboys who did not play computer games at all.…”
Section: Serotonin: the 'Balance' Hormonementioning
confidence: 99%
“…Several cognitive domains appear to be sensitive to changes in serotonin such as memory, attentional functions notably focused and sustained attention, and cognitive flexibility (Schmitt et al, 2006;. Podrigalo et al (2020) examined the metabolic and endocrine changes of forty-five schoolboys engaged in computer gaming. The participants were divided into two groups: the active players' group (n=26) and the control group which consisted Research, Society and Development, v. 12, n. 2, e20512239568, 2023 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v12i2.39568 of 19 schoolboys who did not play computer games at all.…”
Section: Serotonin: the 'Balance' Hormonementioning
confidence: 99%
“…However, the impact of a single session of video gaming attracted much less research interest, giving grounds for quantifying a possible acute metabolic burden of this everpopular form of leisure activity. Recent studies demonstrated a number of biochemical correlates of single-session video gaming [6], including an increase in glucose metabolism and energy expenditure [7], cortisol/catecholamines alterations [8], and oxidant-antioxidant perturbations [9]. Interestingly, no studies so far assessed whether acute video gaming affects creatine metabolism, a metabolic pathway critical in replenishing immediate energy for cells and tissues with high and intermittent energy fluctuations [10].…”
Section: Introductionmentioning
confidence: 99%
“…This microbiota participates in a wide variety of metabolic and immunological functions including differentiation of mucosa, maturation of local immune system, degradation of toxins, maintenance of the proinflammatory and anti-inflammatory balance, provision of "colonization resistance" and prevention of systemic diseases [6,7]. Studies have shown that cigarette smoking contributes to the link between oral microflora dysbiosis and gastrointestinal diseases of tobacco smokers [8][9][10]. Despite well-documented adverse effects of tobacco consumption, cigarettes use is still rising in Ukraine and part of the increase is related to the popularization of alternative electronic nicotine delivery devices, such as electronic cigarettes (ECs).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are studies that address the tobacco cigarettes, dokha and shisha smoking effects on oral microbiota [9,12,13]. However, information about the effect of EC aerosol exposure to oral bacteria remains scarce and limited to a small number of species isolated in culture media [14].…”
Section: Introductionmentioning
confidence: 99%